Effect of steam and sulfur dioxide on sulfur trioxide formation during oxy-fuel combustion. (December 2015) - Wang, Xiaopeng; Liu, Xiaowei; Li, Dong; Zhang, Yu; Xu, Minghou
Highlights: Steam in the flue gas can inhibit SO3 formation by competing O radical with SO2 . SO3 concentration achieves a maximum value at 950 °C with temperature increasing. An increasing SO2 concentration can significantly increases SO3 formation. Abstract: The purpose of the present study is to clarify the effects of temperature, initial SO2 concentration and steam addition on SO3 formation under oxy-fuel combustion. The experiments consisted of two parts. The first part was the homogeneous experiment conducted with the simulated flue gas in a horizontal tube furnace. In order to further study the formation characteristics of SO3 in the heterogeneous gas atmosphere, the other part of the experiments was carried out by using a high-sulfur coal and a low-sulfur coal respectively in a drop tube furnace. The experiment results indicated that SO3 concentration increased first but then decreased with the temperature increasing, and the maximum SO3 concentration appeared at around 950 °C. The increase of initial SO2 concentration could significantly enhance SO3 formation. But the injected steam inhibited SO3 formation in all test cases obviously, as the injection of steam could increase the kinds of the radical pool compositions in the flue gas, which might involve more complex interactions with the formed SO3 during wet recycling. Moreover, compared to the former homogeneous experiment, the latter presented a more intense inhibiting behavior, which was probably attributed to the more diversification of the radical pool compositions in pulverized-coal combustion.